2004
DOI: 10.1002/jmv.20045
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia in HIV‐infected patients in the HAART era: Incidence, risk, and impact of the pneumococcal vaccination

Abstract: The objective of this study was to assess the factors implicated in an increased or decreased risk of pneumonia, with particular attention to the response to highly active antiretroviral therapy (HAART) and the effect of the polysaccharide 23-valent pneumococcal vaccination in 300 human immunodeficiency virus (HIV)-infected adults followed-up for a median of 35.6 months. Pneumococcal pneumonia occurred in 12 patients and all bacterial pneumonia (pneumonia caused by Streptococcus pneumoniae or other bacteria, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 30 publications
0
41
0
1
Order By: Relevance
“…1c) [16,17]. Studies finding no vaccine effect were the previously mentioned randomized trial [14,35] and the study by Ló pez-Palomo et al [39]. In the latter study, details of the multivariate analysis of vaccine effectiveness were not reported, but it did show an effect of PPV-23 on allcause pneumonia.…”
Section: All-pneumococcal Diseasementioning
confidence: 95%
See 3 more Smart Citations
“…1c) [16,17]. Studies finding no vaccine effect were the previously mentioned randomized trial [14,35] and the study by Ló pez-Palomo et al [39]. In the latter study, details of the multivariate analysis of vaccine effectiveness were not reported, but it did show an effect of PPV-23 on allcause pneumonia.…”
Section: All-pneumococcal Diseasementioning
confidence: 95%
“…Two found no significant effect [35,39], three found a protective effect [19,32,36], and two found a protective effect in subgroups with high CD4 cell counts at the time of immunization (Fig. 1c) [16,17].…”
Section: All-pneumococcal Diseasementioning
confidence: 97%
See 2 more Smart Citations
“…The 23 valent polysaccharide vaccine appears to be effective in HIV infected persons in North America for reducing all cause pneumonia but those with plasma viral load of greater than 100,000 may not benefit 180 , 181 , 182 , but the results of clinical trials have not always been consistent 183 . On the other hand African patients have not been documented to benefit from the 23 valent pneumoccal vaccine, 184 , 185 .…”
Section: Preventionmentioning
confidence: 99%